“’Whose Dog are You?’” Union Army Pets in the American Civil War, 1861-1865 - Combes, McKenzie A. (Kansas State University. Dept. of History, 2018)
This is an analysis of the importance and use of Union Army pets during the American Civil War from 1861-1865. Research shows that pets provided psychological advantages, companionship, and a meaningful, necessary relationship with their fellow soldiers. Research also shows that these pets were held to the same standards as the soldiers and were treated and acted just like any other soldier. The author used letters, diaries, studies, journal articles, reports, photographs, and books.
Keywords: Dogs; Military; Psychology; Companionship; Battles; Morale